Hebdomadaires de bandes dessinées et imaginaires médiatiques dans les années 1950–1960 - Alexis Lévrier (Comicalités)
This article looks at the place of comic strip magazines from the 1950s–1960s in media culture, and more specifically in the history of the press. It shows that, while the hybridity of these periodicals is undeniable, the alternation between editorial pages and comic strips does not prevent the cohesion of this singular editorial object. This unity is based in particular on the implementation of a transmedia system, which closely combines pre-publication comics with content borrowed from the cinema, radio and television. But these magazines belong above all to the world of the press: they are imbued with the same imagination of journalism, which transcends the boundaries between editorial and comics, or between reality and fiction. Readers themselves are constantly associated with this imaginary world, to the point of being portrayed as reporters in the making, destined to follow in the footsteps of journalistic heroes.